Leveraging Digital Marketing For Traditional Grocery Businesses - Wicaksono, Soetam Rizky; Broto, Felik Sad Windu Wisnu; Hariyono, Patricia Ibi (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study examines the implementation of digital marketing strategies in a traditional grocery distributor in Malang, Indonesia, operating with conventional methods. The research, conducted from June to September 2023, follows an action research methodology encompassing identification, design, implementation, and evaluation stages. The initial identification phase, through interviews and observations, highlighted the distributor's limited customer reach, necessitating a digital marketing approach for market expansion. The subsequent design phase involved creating tailored content for social media platforms like TikTok and Instagram, including product photos, videos, and storytelling in captions. The strategy implementation stage saw these plans executed, with significant content posted across platforms and the successful integration of an e-catalogue and Google Business for enhanced online visibility. The project evaluation revealed increased customer engagement on social media, indicating effective strategy implementation. However, challenges in quantitatively assessing direct sales impact due to the distributor's traditional operation model were noted. The study suggests that while immediate sales increases were not definitively measured, the strategy laid the groundwork for future growth and market expansion. The research highlights the importance of digital marketing for traditional businesses in adapting to the digital era and underscores the necessity of establishing clear KPIs for effective strategy evaluation..